Analisis Total Bakteri Coliform Di Perairan Pelabuhan Lembar - Amalia Dewani Putri; Paryono Paryono; Sholihati Lathifa Sakina (Universitas Mataram, 2026)
Port waters are coastal areas vulnerable to environmental pressure due to shipping activities, coastal settlements, and beach utilization. This study aimed to identify total coliform bacteria in the waters of Lembar Port and compare the results with the applicable seawater quality standard. The study was conducted from August to September 2025 at five sampling stations representing different activity zones, namely Lembar Port dock, Gili Mas dock, ship parking area, Cemare Beach, and a control area. Seawater samples were collected purposively at a depth of 10–20 cm and analyzed in the laboratory using the Most Probable Number (MPN) method. Temperature and pH were measured as supporting parameters, while data on ship activity and community sanitation were used as contextual information. The results showed that all sampling stations had total coliform values of <1.8 MPN/100 mL. These values were far below the seawater quality standard of 1,000 MPN/100 mL. Water temperature ranged from 29 to 30.7°C, while pH ranged from 7.71 to 8.19. Ship traffic remained active during the study period, but it was not followed by an increase in measurable total coliform. Limited interviews also indicated that households in the surrounding villages had toilets with septic tanks. Therefore, the microbiological quality of Lembar Port waters during the observation period still met the seawater quality standard for total coliform and may serve as baseline data for future port water quality monitoring.